1988
DOI: 10.1007/bf02549574
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of renal complications in Schönlein—Henoch purpura syndrome in dependence of an early administration of steriods

Abstract: Between 1976 and 1986, the authors treated 33 children with Schönlein-Henoch purpura (S-H purpura), with physiological urinary finding on admission. Twenty-three of them received prednisone already at the beginning of hospitalization, 10 were not given any prednisone at all. In patients with prednisone, nephropathy occurred only once (4.3%), in those without prednisone it occurred 5 times (50%), the incidence being thus significantly higher. Prednisone was administered in doses ranging between 1.0 and 2.5 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
3

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 5 publications
2
17
0
3
Order By: Relevance
“…AP = anaphylactoid purpura demonstrated in controlled trials [1], about 12 years ago we began a prospective study in AP patients without nephropathy. The preliminary positive results of this study were presented in 1980 [18] and confirmed in 1988 by Buchanec et al [5]. We now present our final results and conclusions.…”
Section: Offprint Requests To: F Mollicasupporting
confidence: 91%
“…AP = anaphylactoid purpura demonstrated in controlled trials [1], about 12 years ago we began a prospective study in AP patients without nephropathy. The preliminary positive results of this study were presented in 1980 [18] and confirmed in 1988 by Buchanec et al [5]. We now present our final results and conclusions.…”
Section: Offprint Requests To: F Mollicasupporting
confidence: 91%
“…The difference in the prevalence of nephropathy between the two groups was statistically significant (P<0.001). Our results, first presented in 1980 by Mollica et al [9], were confirmed in 1988 by Buchanec et al [10] and in 1998 by Kaku et al [11]. In contrast, Saulsbury [12], in a retrospective study, remarked that early corticosteroid therapy did not prevent delayed nephritis in children with HSP, although Robson and Leung [13] agreed with our treatment strategy.…”
supporting
confidence: 63%
“…Retrospective and prospective studies have reported on patients with HSP lacking clinical signs of nephropathy at admission who were treated with prednisone at doses ranging from 1.0 to 2.5 mg/kg per day over a period of 7-21 days. The authors of these preliminary studies concluded that compared to untreated patients, treated children displayed a lower incidence (Δ12-46%) of nephropathy [15][16][17]. A multivariate analysis demonstrated that oral prednisone or intravenous methylprednisolone (MP) prophylaxis (5 mg/kg four to six times per day for 3-5 days) significantly decreased the risk of renal involvement [3].…”
Section: Prevention Of Hspnmentioning
confidence: 95%